Evaluation of interacting length in prediction of over bank flow. Issue 2 (4th May 2017) - Devi, K.; Khatua, K. K.; Das, B. S.; Khuntia, J. R.
Abstract: Study of interaction mechanism in compound channels consisting of main channel with adjoining floodplains is very important for environmental, ecological and design issues. The flow structures at junction between main channel and floodplain are rigorous due to the complex exchange of momentum. It leads to the imprecise quantification of the discharge in compound channel. Many investigators have proposed various discharge prediction methods among which divided channel method is widely acceptable. This current study approaches a simple way to predict discharge in a compound channel by incorporating an interacting length at the interface between the main channel and adjoining flood plains. From the experimental results of NITR channel data and Flood Channel Facility of UK data, the interacting lengths have been estimated for different combinations of flow depths and width ratios. The functional relationships of the interacting length with the non-dimensional hydraulic and geometric parameters have been found out and a multi linear regression model is developed. The performance of present approach has also been evaluated with other standard approaches. The strength of the current model is successfully tested with natural river data.